Conduit systems buried underground for the protection and management of insulated electrical cables or communication cables. Polyethylene (PE), Polypropylene (PP) or Unplasticized poly(vinyl chloride) (PVC-U) conduit systems. Requirements for solid wall conduits, fittings and the system used in special applications Part 2, (31st July 2023) - British Standards Institution,
No abstract available